Bridging the Gap between Land Suitability and Local Wisdom Species in South Sumatra Peatlands, Indonesia - Armanto, M Edi; Wildayana, Elisa (Journal of Smart Agriculture and Environmental Technology, 2025)
The primary issue with peatlands until now was people’s ignorance about land suitability. Changes in patterns and details of the distribution of peatland use based on Local Wisdom Species (LWS) are increasingly  unclear. We don’t know the suitable locations of cultivated LWS, so peatland productivity is declining and degradation continues. This research aims to evaluate land suitability for LWS in South Sumatra peatlands, Indonesia. Local Wisdom Species and soil samples were taken based on the type of peat land uses, and then laboratory work was carried out. Local Wisdom Species showing direct benefit are divided into two groups, namely LWS producing quickly are usually Purun Tikus (Eleocharis dulcis), water spinach (kangkung), bitter melon (paré), floating rice, and auction system for fishing, and LWS recognizing commercially are usually coconut, honeybees, gelam, sago, and jelutong. The level of land suitability of these two groups is S1 (highly suitable); and S2 (moderately suitable) with the only limiting factors being nutrient availability and nutrient retention (except coconut). By using science and technology, such as liming, fertilizing, improving water systems, and avoiding burning, all of these limiting factors can be overcome. Based on local knowledge, four strategies are suggested for sustainable peatland restoration, namely decentralized; conservative; protective; and optimal strategies.